Rapid photoinduced charge injection into covalent polyoxometalate–bodipy conjugates. Issue 25 (6th June 2018) - Black, Fiona A.; Jacquart, Aurélie; Toupalas, Georgios; Alves, Sandra; Proust, Anna; Clark, Ian P.; Gibson, Elizabeth A.; Izzet, Guillaume
Abstract : A series of redox tunable polyoxometalate–bodipy conjugates display variable charge transfer dynamics occuring down to 54 ps. Abstract : Controlled design of photoactive hybrids would provide highly active materials for solar energy conversion and photo(electro) catalysis. We describe the kinetics of photoinduced electron transfer in a series of photoactive hybrids based on Keggin-type polyoxometalates (POMs) covalently grafted to bodipy photosensitizers. We show how the electronic properties and corresponding dynamics of these hybrids can be readily tuned by varying the POM metal ion, the anchoring functionalization and the spacer length. Ultrafast visible and IR transient absorption spectroscopy, supported by spectroelectrochemical measurements, reveals that photoinduced electron transfer from the bodipy chromophore to the organosilyl POM derivative occurs as rapidly as τ = 54 ps to generate a long-lived ( τ = 4.8 ns) charge-separated (CS) state, making this system appropriate for applications in photoelectrochemical devices.